2016
DOI: 10.1115/1.4034993
|View full text |Cite
|
Sign up to set email alerts
|

Multidirectional In Vivo Characterization of Skin Using Wiener Nonlinear Stochastic System Identification Techniques

Abstract: A triaxial force-sensitive microrobot was developed to dynamically perturb skin in multiple deformation modes, in vivo. Wiener static nonlinear identification was used to extract the linear dynamics and static nonlinearity of the force-displacement behavior of skin. Stochastic input forces were applied to the volar forearm and thenar eminence of the hand, producing probe tip perturbations in indentation and tangential extension. Wiener static nonlinear approaches reproduced the resulting displacements with var… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 47 publications
0
1
0
Order By: Relevance
“…During full-text review, study citations were examined, and 20 articles were identified and included. A total of 186 papers 29–31,33–215 were included for data extraction.…”
Section: Resultsmentioning
confidence: 99%
“…During full-text review, study citations were examined, and 20 articles were identified and included. A total of 186 papers 29–31,33–215 were included for data extraction.…”
Section: Resultsmentioning
confidence: 99%